Antifertility activities of srikaya leaves (Annona squamosa L.) ethanol extract against reproduction system : spermatogenesis and quality sperm study - Nur Laili Dwi Hidayati; Tita Nopianti; Yuliana Dewi; Yani Suryani (Pharmaciana, 2018)
Has done research about antifertility activities of Srikaya leaves (Annona squamosa L.) ethanol extracts against reproduction system. There are classified into 4 groups: negative control (suspension PGA 1%), I dose (0.00448 g/200 g BW rat), II dose (0.00967 mg/200 g BW rat), and III dose (0.01934 mg/200 g BW rat). Administration of the test preparation is done orally for 48 days. Parameters observed were spermatogenesis and quality of sperm. Spermatogenesis parameters measured were testis index (%), seminiferous tubule diameter (Âµm), the number of spermatogonia and spermatocytes cells. Spermatozoa quality parameters measured were sperm motility, concentration, and morphology. Study parameters were statistically analyzed using ANOVA. The results showed that ethanol extract of Srikaya leaves can lower the index of the testis and seminiferous tubule diameter, decrease the number of spermatogonia and spermatocytes cells significantly. The ethanol extract of Srikaya leaves can reduce sperm motility, concentration, and increasing abnormality significantly.